Bidding decision in multi-attribute reverse auction. (20th October 2010) - Ray, Arun Kumar; Jenamani, Mamata; Mohapatra, Pratap K.J.
We design a decision making model for solving the bidding problem in a sealed bid multi-attribute reverse auction. Bidders in reverse auctions face the problem of decrementing the bid in every round until the final round. Although the bidders receive information from the previous rounds regarding the winning bid, but the decision regarding the bid-decrement is purely subjective. Considering the fuzziness in the available information and the subjective parameters, we develop a new bidding algorithm for multi-attribute reverse auctions using multi-stage fuzzy game technique. In this work, we present the fuzzy decision making model and use this to develop the bidding algorithm for multi-attribute reverse auction. We illustrate the use of the algorithm through an example. The agent using the fuzzy bidding algorithm is able to decide the bid intelligently in every round of the auction. The algorithm may be used by the agents to take bidding decisions adaptively in repeated auction scenario.